Effect of arbuscular mycorrhizal fungi on early growth, root colonization, and chlorophyll content of North Maluku nutmeg cultivars - Sulistiono Wawan; Aji Himawan Bayu; Handoko Sigid; Lase Jonathan Anugrah; Suryanti Suryanti; Apriyana Yayan; Rizal Molide (Open Agriculture, 2023)
This study aimed to investigate the agronomic traits of nutmeg transplanting by arbuscular mycorrhizal fungi (AMF) inoculation. The low-fertility soil of Sofifi North Maluku was subjected to a slow early growth stage of nutmeg cultivars. A completely randomized design was used in the experiment. The first factor was three different AMF doses: 0, 4, and 8 g seedlings−1. The second factor consisted of three cultivars: “Ternate 1,” “Tobelo 1,” and “Makian.” Root colonization and agronomic traits were measured 28 weeks after inoculation and transplantation. Results showed that AMF inoculation increased the AM colonization by 2.5–39.0%, significantly increased the leaf area (LA) (p < 0.01) in all cultivars, and interacted with cultivars to increase chlorophyll a (Chl a) (p < 0.05), chlorophyll b (Chl b) (p < 0.01), and total Chl (p < 0.01). Cultivars “Makian” showed the highest Chl (188.4%) at 8 g seedling−1 doses of AMF that were significantly (p < 0.01) different from the cultivar “Tobelo 1” at the same dose. The largest mycorrhizal response was found in the cultivar “Ternate 1” (biomass increase of 30–37.0%). The cultivar “Ternate 1” produced the largest LA (36.7–106.9%) and shoot dry weight (27.8–45.8%) that were significantly (p < 0.01) different from the other cultivars. The percentage of AM colonization was strongly determined (R 2 = 0.88) by Chl a, Chl b, and K content in leaves. This technology is a breakthrough to increase LA and plant biomass in the early growth stage of nutmeg cultivation.